Exploring Influence of Production Area and Harvest Time on Specialized Metabolite Content of Glycyrrhiza glabra Leaves and Evaluation of Antioxidant and Anti-Aging Properties - Teresa Docimo; Rita Celano; Alessia Lambiase; Rosa Di Sanzo; Simona Serio; Valentina Santoro; Paola Coccetti; Mariateresa Russo; Luca Rastrelli; Anna Lisa Piccinelli (MDPI AG, 2024)
Calabrian Glycyrrhiza glabra is one of the most appreciated licorice varieties worldwide, and its leaves are emerging as a valuable source of bioactive compounds. Nevertheless, this biomass is usually discarded, and its valorization could contribute to boost the economic value of the licorice production chain. In this study, the effects of production area and harvest time on the specialized metabolite content of G. glabra leaves (GGL) and also the antioxidant and anti-aging properties are evaluated to explore the potential of this untapped resource and to select the most optimal harvesting practices. GGL exhibited high levels of specialized metabolites (4-30 g/100 g of dry leaf) and the most abundant ones are pinocembrin, prenylated flavanones (licoflavanone and glabranin), and prenylated dihydrostilbenes. Their levels and antioxidant capacity in extracts are influenced by both production area and harvest time, showing a decisive role on specialized metabolites accumulation. Interestingly, GGL extracts strongly attenuate the toxicity of α-synuclein, the intracellular reactive oxygen species (ROS) content, and cellular senescence on Saccharomyces cerevisiae expressing human α-synuclein model, showing great potential to prevent aging and age-related disorders. These results provide insights into the phytochemical dynamics of GGL, identifying the best harvesting site and period to obtain bioactive-rich sources with potential uses in the food, nutraceutical, and pharmaceutical sectors.